Pentingnya Manajemen Strategi pada Perusahaan Sebagai Media Pengambilan Keputusan - fitrohcahya, rahmadani aidil (Maliki Interdisciplinary Journal, 2025)
Strategic management is a key element in corporate decision making and is used to guide and optimize organizational performance. This article explains the important role of strategic management in developing the company’s vision, mission and goals as well as analyzing internal and external conditions using techniques such as SWOT analysis. With a systematic approach, strategic management helps companies identify opportunities and risks and use resources efficiently. In addition, a continuous evaluation and control process ensures that the strategies implemented remain relevant to market trends. This allows companies to increase competitiveness, adapt to change, and drive innovation. This article also includes suggestions for improving managers’ understanding, conducting regular SWOT analysis, and encouraging team collaboration in strategic decision making. Therefore, strategic management not only functions as a planning tool but also as a control mechanism that is important for the sustainability and operational success of the company.